2014
DOI: 10.1109/tmtt.2014.2327199
|View full text |Cite
|
Sign up to set email alerts
|

Microstrip-Ridge Gap Waveguide–Study of Losses, Bends, and Transition to WR-15

Abstract: This paper presents the design of microstrip-ridge gap waveguide using via holes in PCBs, a solution for high frequency circuits. The study includes how to define the numerical ports, pin sensitivity, losses, and also a comparison with performance of normal microstrip line and inverted microstrip lines. The results are produced using commercially available EM simulators. A WR-15 to microstrip-ridge gap waveguide transition was also designed. The results are verified with measurements on microstrip-ridge gap wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(56 citation statements)
references
References 13 publications
0
55
0
1
Order By: Relevance
“…However, new versions of gap waveguide transitions are required as the frequency increases. Several suitable transitions working at 60 GHz have been already studied and experimentally validated [12], [13]. In addition, some investigations on transitions between a ridge gap waveguide and standard rectangular waveguides at 0.3 THz have been also initiated.…”
Section: Introductionmentioning
confidence: 99%
“…However, new versions of gap waveguide transitions are required as the frequency increases. Several suitable transitions working at 60 GHz have been already studied and experimentally validated [12], [13]. In addition, some investigations on transitions between a ridge gap waveguide and standard rectangular waveguides at 0.3 THz have been also initiated.…”
Section: Introductionmentioning
confidence: 99%
“…Losses for the microstrip gap waveguide (with dielectric) has been reported in [60]. This study is very interesting, hence it is demonstrated that microstrip gap waveguide has less loss in comparison with the conventional microstrip line.…”
Section: Study Of Losses -Methodsologymentioning
confidence: 59%
“…In As it is explained in [46], by keeping the period and via-hole diameter fixed, an increase in the pad diameter will shift the stop-band toward lower frequencies. In previous works [47], it is related that the pins surface is more suitable than mushroom surface at high frequency, due their physical implementation and volume.…”
Section: Design Of the Microstrip Gap Waveguide Compatible With Pcb Omentioning
confidence: 99%
“…More recently, in [787], characterization and study of MRGW losses is afforded at the more challenging operation frequencies of V-band: the designed mushroom structure creates a stopband from 45 GHz to 72 GHz. In this work, long lines, including bends are used to obtain the losses in the usual way, instead of resonators.…”
Section: Study Of Lossesmentioning
confidence: 99%
“…Two transitions are designed: SSGW to WR-15, and microstrip packaged with GW technology (later explained in section 8.2.2.7) to WR-15. Regarding to the SSGW to WR-15 transition, it is highlighted that the test-fixture of [859] presents the problem of having the rectangular waveguide extending vertically upwards from the top side of the PCB, whereas for antenna applications it is more convenient extend it downwards, as it is done in [787], for instance. The work improves a previous design [867] that uses a patch (as in or [856] or [857]), for the excitation of a rectangular waveguide.…”
Section: (D)mentioning
confidence: 99%